Anti-inflammatory, antioxidant and anti-virulence roles of atractylodin in attenuating Listeria monocytogenes infection - Xu, Lei; Zhou, Yonglin; Xu, Jingwen; Xu, Xiangzhu; Lu, Gejin; Lv, Qianghua; Wei, Lijuan; Deng, Xuming; Shen, Xue; Feng, Haihua; Wang, Jianfeng (Frontiers in Immunology, 2022)
Background: Listeria monocytogenes (L. monocytogenes), as a pandemic foodborne pathogen, severely threatens food security and public health care worldwide, which evolves multiple bacterial virulence factors (such as listeriolysin O, LLO) for manipulating the immune response of L. monocytogenes-host interactions. Methods: Hemolysis assay was employed to screen a potential LLO inhibitor and the underlying mechanisms were investigated using molecular dynamics (MD) simulation and oligomerization assay. The effects of candidates on immune response were examined by qRT-PCR and immunoblotting analysis. Histological analysis, ELISA assay and biochemistry detection were conducted to assess in vivo efficacy of candidates. Results: In the present study, natural terpenoid atractylodin was characterized as an alternative drug candidate for the treatment of L. monocytogenes by the regulation of LLO function and host Nrf2/NLRP3 signaling pathway. Notably, in vivo infection model by L. monocytogenes also highlighted that atractylodin treatment provided effective therapeutic benefits, as evidenced by decreased bacterial burden and diminished inflammation. Congruently, the survival rate of L. monocytogenes-infection mice increased significantly from 10.0% to 40.0% by atractylodin treatment. Conclusion: Collectively, our study showed for the first time that atractylodin has tremendous potential to attenuate L. monocytogenes pathogenicity by blocking LLO pore formation and mediating the suppression of inflammation and oxidative stress, providing a promising therapeutic strategy and broadening the applications of atractylodin against L. monocytogenes infection.